PHANEROZOIC COPPER AND PRECIOUS METAL ORE FORMATIONS OF THE EAST EUROPEAN PLATFORM - Chaikin V.G.; Glebashev S.G.; Meskhi A.M.; Zakirova F.A. (My University, 2004)
Based on ore-formation analysis, the distribution and deposition conditions of exogenic copper and precious metal (Ag, Pt, Pd, Au) ores within the sedimentary cover of the East European Platform are examined. Three main ore formations are defined: copper, precious metal-copper, and precious metal. Their deposition in metallogenic zones with different mineralization was determined by tectonomagmatic activation during the Caledonian, Hercynian, and Alpine stages of the platform development. The Hercynian stage was characterized by the minimal scale of stratiform mineralization and the widest metallogenic profile of copper and precious metals. Of the main geodynamic settings, represented by continental rifts, interrift blocks, and superimposed marginal troughs, interrift blocks were most favorable for the formation of commercial hydrogene mineralization.